Pastoral Counseling for Congregants Experiencing Fear of Missing Out Due to Social Media - Gede Widiada; Sara Do Hina; Apin Militia Christi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Fear of Missing Out (FoMO) has become a significant psychosocial and spiritual concern among congregants whose daily rhythms are shaped by social media visibility, comparison, and constant connectivity. This article examines FoMO as an object of pastoral counseling, not merely as excessive screen use but as a relational and affective pattern in which digital platforms intensify unmet needs for belonging, identity, autonomy, and meaningful participation. The study aims to construct a pastoral counseling approach for congregants who experience anxiety, compulsive checking, social comparison, diminished self-worth, and spiritual distraction because of social media. Methodologically, the article uses a constructive-integrative literature review, synthesizing peer-reviewed research on FoMO, problematic social media use, social comparison, self-determination theory, and spiritually integrated counseling alongside major works in pastoral care and practical theology. The synthesis indicates that FoMO is best understood as a need-frustration cycle that is amplified by passive browsing, online comparison, and algorithmic immediacy. Pastoral counseling can respond constructively through careful assessment, theological reframing of identity and belonging, digital habit formation, communal practices, and referral pathways when psychological risk is present. The article concludes that pastoral counseling is uniquely positioned to transform FoMO from anxious digital vigilance into discernment, embodied community, and spiritually grounded digital wisdom.